The potential of implementing property tax incentives on green building in Malaysia - Ab. Azis, Shazmin Shareena (2013)
Green building concepts are widely accepted and practiced worldwide. The aim of green building is to reduce building impact on environment and human health and in a meantime conserve natural resources. Many initiatives have been carried out in order to support green building development. Many incentives has been offered and provided as a means to support the development of green buildings in Malaysia. The participation of local authority in supporting green buildings is very sound. As an initiative, the local authority can participate in green building by providing property tax incentives on green building within their jurisdiction area. United Stated has applied and implemented property tax incentives on green buildings earlier since year 1975. There are 3 types of model that have been applied in 44 counties in US which are property tax exemption, property tax reduction and property tax credit. Nevertheless, each of these models was developed according to LEED’s green criteria. Whereby Malaysia are using GBI green criteria as listed in GBI’s Malaysia. Therefore, this paper focus on entitle technology or component on each LEED’S green criteria that been used in property tax incentives in order to establish property tax incentives according to GBI on green buildings in Malaysia. This is essential in order to explore the potential of property tax incentives on green building to be implementing in Malaysia.